Konsep Aliran Filafat Pendidikan Rekontruksionalisme - Hannan, Siti; Dina, Risma Norma; Khatimah, Husnul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This journal discusses the concept of reconstructionism in education, a school that views education as a tool to change unjust social structures and create a better society. The journal also discusses examples of the application of reconstructionism in education, such as the discussion of social issues, social projects, and critical education. In addition, the article also discusses criticisms of reconstructionism, including idealism, lack of focus on learning, and the potential for manipulation. The journal concludes that reconstructionism is an important educational school to consider in the context of social change. It offers a perspective that is critical of the status quo and encourages students to be actively involved in the process of change. However, it is important to consider the criticisms of this school and find ways to effectively apply it in practice.